Minocycline sensitivity related to the phage type of multiply resistant staphylococci. - Rich, G (1975)
Clinical isolated of multiply antibiotic-resistant strains of Staphlococcus aureus were divided into three groups by phage typing. The most prevalent type, which is usually cloxacillin resistant, was found to be moderately sensitive to minocycline. Unfortunately the degree of sensitivity is not sufficient to warrant the use of the antibiotic in severe staphlococcal infection.